Understanding the multi-scale structure, physicochemical properties and in vitro digestibility of citrate naked barley starch induced by non-thermal plasma. Issue 17 (22nd July 2021) - Shen, Huishan; Ge, Xiangzhen; Zhang, Bo; Su, Chunyan; Zhang, Qian; Jiang, Hao; Zhang, Guoquan; Li, Wenhao
Abstract : Plasma pretreatment promoted the citrate esterification of naked barley starch. Plasma pretreatment increased the degree of substitution and resistant starch content, while reducing the molecular weight and long amylopectin chains of citrate starch. Abstract : Non-thermal plasma treatment is an emerging and effective starch modification technique. In this paper, plasma pretreatment was used to modify citrate naked barley starch for enhancing the ability of citric acid to access the starch structure. Plasma treatment did not alter the granule morphology and crystalline type of starch, but degraded the starch molecules and caused more short chains. Plasma pretreatment could etch the starch surface and depolymerize the starch molecules, which increased the accessibility of citric acid for uniform hydrolysis in the subsequent esterification reaction. Therefore, plasma pretreatment significantly promoted the structural and physicochemical modification of the citrate starch, including the enhancement of the degree of substitution, the short-range ordered degree and gelatinization temperatures, and the decreases in the molecular weight, long chains of amylopectin and pasting viscosities. Meanwhile, plasma pretreatment improved the efficiency of acid hydrolysis and decreased the enzymatic digestibility, so that it showed a higher resistant starch content in comparison with its corresponding citrate starch. This paper could provide a new insight into the lower digestion rate and improved functional properties of citrate starch.